IMPROVEMENT OF EARLY MATURITY IN RICE VARIETY BY MARKER ASSISTED BACKCROSS BREEDING OF Hd2 GENE - Fatimah Fatimah; Joko Prasetiyono; Ahmad Dadang; Tasliah Tasliah (Indonesian Agency for Agricultural Research and Development, 2014)
Early-maturing and high-yielding rice variety is very useful for increasing rice production in Indonesia. The aim of this research was to develop new lines of Indonesian rice containing Hd2 gene using Code variety as a recipient parent and Nipponbare variety as a donor parent through targetted MAB approach using RM1362 and RM7601 in chromosom 7 for foreground selection. After two generations of backcrossing, the positive alleles of Hd2 gene from Nipponbare had successfully trans-ferred into Code. The plant number CdNp_29 in BC2F2 popula-tion had the highest genome recovery of 82.7%. The twelve BC2F3 plants were selected for self-pollination to generate BC2F4. These selected lines that carried the Hd2 gene were screened in the greenhouse for the evaluation of heading date and agronomic traits. All improved lines had Hd2 gene similar to the donor parent Nipponbare. The heading date of the breeding lines ranged from 73 to 89 days (Code 85 days) or fill the third criterion of rice maturity that is 103-104 days compared to Code of 116-119 days, whereas their agronomic performances were similar with that of Code. Application of MABc for im-proving rice early maturity has accelerated the development and selection in early generation of superior lines having genetic background of Code. It is expected that the newly developed lines of Code will be utilized to increase rice production in Indonesia.